Alternativas de manejo de lactancia en vacas Brahman Anéstricas para mejorar índices reproductivos y económicos. - Salazar Espinel, Carlos Julio (2016)
Management alternatives calf in Ecuador are practices that are used to improve reproductive performance in female cattle meat. In order to assess the reproductive and productive parameters in anestric Brahmán cows with calf management options, 15 cows and their calves in groups of three were used, it was used to design a randomized complete block (DBCA), the treatments were: Traditional weaning (T0), restricted suckling (T1), early weaning (T2).The variables studied were weaning zeal interval (IDC) and delivery zeal interval (CPI) in days, ovulatory zeal (CO), pregnancy rate (TP) and weight calves (PB). The average scores were: 150.40 ± 2.61 days (IDC) and 220.40 ± 2.61 days (CPI) for t0; 59.60 ± 3.26 days (IDC) and 129.60 ± 3.26 days (CPI) for t1, while that for T2 were 8.60 ± 1.02 days (IDC) and 78.60 ± 1.02 days (IPC) (p <0.05). Ovulatory estrus reached 100% at T0 (p <0.05) while (TP) was 100% for T1 (p <0.05). Calves greater weight gain were obtained with T2 163,80kg which was highly significant value. It is concluded that the best reproductive and productive performance is achieved with T2.